The museum in the newspaper : a survey of Straits Times coverage of the Raffles Museum, 1845-1965 - Loo, Qi Ying (2018)
This project considers the public’s image of Singapore’s Raffles Museum during the colonial period, and the evolution of this image starting from the inception of the museum to the emergence of Singapore as an independent nation. A local English-language newspaper, the Straits Times, is used as a proxy for the views that members of the public held on the museum in the years under study. The project takes advantage of the newspaper archives, a significant proportion of which have been digitized by the National Library of Singapore, and have been made publicly available and searchable. All articles containing mention of the Museum were summarized and then analysed to reconstruct a view of the themes and trends that the public, through the lens of the Straits Times, held about the Museum. These themes and trends offer a reflection of the Singapore public and its society in colonial times, as well as the blossoming international field of museology of which the Raffles Museum was a regional representative. To some extent, press coverage of the museum also mirrors the progress of Singapore from its mercantile colonial origins to self-government and independence.